Prevalencia de insuficiencia renal crónica en la población de influencia del Hospital de Apoyo Cayetano Heredia: 1982- 1984. - Figlio, Gino; Cieza, Javier (Revista Médica Herediana, 2014)
In order to find out the prevalence of chronic renal failure (CRF) in our country, we made this retrospective study. We evaluated all patients with CRF controlled at the “Hospital de Apoyo Cayetano Heredia” coming from its influencing area, between 1982 and 1984. The prevalence rate was definitely lower than other countries. We found 37.7 cases /million. The prevalence rate was higher in females. It also had age correlation.